Revealing the Key Drivers Conducive to the “Once‐In‐A‐Century” 2021 Peninsular Malaysia Flood - Luojie Dong; Jingyu Wang; Xiefei Zhi; Edward Park; Xianfeng Wang; Steve Hung‐Lam Yim; Hugh Zhang; Joshua Lee; Dung Duc Tran (Geophysical Research Letters, 2023)
Abstract In December 2021, Super Typhoon Rai caused significant devastation to the South Philippines and East Malaysia. In the meantime, an unprecedented flood event occurred in Peninsular Malaysia at 2,000 km west of the typhoon's path, causing comparable socioeconomic impacts as Rai. Record‐breaking 3‐day precipitation was received by Peninsular Malaysia during 16–18 December. Based on the storm tracking results, this study identified two mesoscale convective systems (MCSs) that were directly responsible for the flooding. The two MCSs were directly initiated by a tropical depression and sustained by an elongated easterly water vapor corridor originating from the Super Typhoon Rai. The return period and joint frequency analysis of key drivers indicate that the 3‐day downpour was more severe than a “once‐in‐a‐century” event. Historical records suggest such anomalous moisture channel has become more frequent in Southeast Asia, which alarms heightened attention in forecasting winter flood.